2000
DOI: 10.1007/s002160050048
|View full text |Cite
|
Sign up to set email alerts
|

Determination of dichloroacetic acid and trichloroacetic acid by liquid-liquid extraction and ion chromatography

Abstract: An extraction technique using MTBE (methyl tert. butyl ether) and reagent water in combination with ion chromatography and conductivity determination was developed to quantify dichloroacetic acid (DCAA) and trichloroacetic acid (TCAA) concentrations in raw water after chlorination. The detection limit of the method was 0.45 and 1.50 microg/L for DCAA and TCAA, respectively. Mean values of recovery ranged from 90 to 96% for DCAA and 95 to 108% for TCAA. The evaluation of recovery and precision of the method ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Using this method, the authors were able determine that their batches of MCA were no longer contaminated with DCA after making improvements in their process for making MCA. Ko et al (2000) developed a method for the analysis of DCA and TCA in drinking water using an ion chromatograph and electrochemical detector. A 200 mL aqueous sample was acidified to pH <0.5 with HCl and extracted with two 15 mL portions of MTBE.…”
Section: Ion Chromatographymentioning
confidence: 99%
See 2 more Smart Citations
“…Using this method, the authors were able determine that their batches of MCA were no longer contaminated with DCA after making improvements in their process for making MCA. Ko et al (2000) developed a method for the analysis of DCA and TCA in drinking water using an ion chromatograph and electrochemical detector. A 200 mL aqueous sample was acidified to pH <0.5 with HCl and extracted with two 15 mL portions of MTBE.…”
Section: Ion Chromatographymentioning
confidence: 99%
“…Similarly, many studies using an HPLC fitted with a conductivity detector can be found in the literature, because HPLC is a good separation technique for water-soluble analytes (including ions). Two ion chromatography methods for the analysis of HAAs in water (Qu and Mou, 1999;Ko et al, 2000) and one HPLC method using a conductivity detector for the analysis of DCA in plasma and urine (Narayanan et al, 1999) are discussed in this review.…”
Section: Conductivity Detectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed evaluation of this method and quality assurance data are discussed elsewhere [15]. Then the aqueous sample was serially extracted with two 15-mL portions of MTBE (methyltert-butylether).…”
Section: Thmmentioning
confidence: 99%
“…The samples were analyzed without dilution with the equipment described in detail and its application in previous papers [15,[17][18][19]. The samples were analyzed without dilution with the equipment described in detail and its application in previous papers [15,[17][18][19].…”
Section: Aoxmentioning
confidence: 99%